La chevelure féminine et la religion (au Tibet) : entre renoncement et pouvoir - Nicola Schneider (Ateliers d'Anthropologie)
This article examines the female side of religious hair in Tibet, which can be separated into two categories: that of Buddhist nuns with shaved heads, and that of the khandroma [mka’ ’gro ma] or “saints” who don hair that is often quite long and abundant. Whereas nuns give up their hair during a more or less formal ceremony as a sign of detachment from the world, the khandorma’s hair holds some of their magic power, and can therefore function as a kind of substitute for the woman in magic rites, or as a relic bringing benedictions and protections to the person who possesses it.